Optimalisasi Pengelolaan Zakat Baznas Jember dalam Mengurangi Kemiskinan di Kampung SDGs Sukorejo Bangsalsari Jember - Ade Faizin; Imam Turmudi (Fakultas Dakwah UIN KHAS Jember, 2022)
BAZNAS Jember is an official institution that was established in August 2017, through the Regent's Decree Number: 188.45/445/1.12/2017 concerning the Appointment of the Head of BAZNAS Jember Regency to carry out the task of managing Zakat, Infaq and Alms in Jember Regency. Optimization is a process to optimize a solution so that the best solution is found from a set of existing alternative solutions. In this case, each zakat institution has its own way of optimizing its performance. The focus of the research in this thesis is how to optimize the zakat management of BAZNAS Jember in reducing poverty in the SDGs Sukorejo village, Bangsalsari Jember and how big the role of BAZNAS Jember zakat in alleviating poverty in the SDGs Sukorejo village, Bangsalsari Jember. The research method uses a participatory qualitative descriptive approach. The research subject uses a purposive sampling technique. Data collection techniques using observation, interviews and documentation. The data analysis of this thesis uses three steps, namely data reduction, data presentation and verification/conclusion. Meanwhile, the validity of the data used triangulation of sources and triangulation of techniques. The results of this study indicate that: 1. In optimizing the management of zakat in reducing poverty in SDGs Sukorejo Village, Bangsalsari Jember, BAZNAS Jember distributes zakat in two ways, namely consumptively and productively. 2. How big is the role of BAZNAS Jember zakat in reducing poverty? In SDGs Village Sukorejo Bangsalsari Jember, the role is very large seen from the achievements of the program that has been carried out by BAZNAS Jember, namely in the form of direct and indirect assistance, consumptive and productive zakat assistance. One example of BAZNAS Jember's assistance in SDGs Village Sukorejo Bangsalsari Jember is providing entrepreneurship training for mother's laundry soap and is currently a permanent production of SDGs Village Sukorejo Bangsalsari Jember.